Penguatan kelembagaan; Eksistensi BUMDes Desa Tarai Bangun pada masa pandemi 2021 - Zaili Rusli; Geovani Meiwanda; Dadang Mashur; Mayarni Mayarni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This article is the result of community service activities, which were carried out at the Bumdes Taiba Smart in Tarai Bangun Village, Kampar. The focus of community service activities carried out is the strengthening of the Bumdes Taiba Smart institution, which is geographically located on the border of Pekanbaru City and Kampar Regency. The Bumdes institutions that exist there basically already have an organizational structure and coexist well with the village government, but there are some challenges that are difficult to solve so that they require brainstorming carried out in community service activities. This community service is through a pattern of brainstorming and regular assistance within 3 months with an offline and online pattern, because there are limitations during July – September 2021, there is a PPKM policy to suppress the Covid 19 pandemic. The challenges found are increasingly difficult for Bumdes Tarai Bangun especially during the pandemic At this time, there was a transition in the community's economy in several sectors. There is not too much local potential that can be utilized and the activities of the Bumdes Taiba Smart are less varied. However, indeed, this community service activity is still not maximal, but it has been able to provide restoration and institutional strengthening for the Taiba Smart Bumdes.